How can we improve tax incentives for charitable giving? Lessons from field experiments in fundraising - Maja Adena (The Routledge Handbook of Taxation and Philanthropy, 2021)
There are several design elements shared between the treatment of donations in the tax code and fundraising strategies. Due to these similarities, law makers wishing to improve tax incentives for charitable giving can draw inspiration from field experiments in fundraising. This is especially relevant since tax return data offer a limited basis for causal conclusions, and real-world experiments with the tax code are not feasible. In this chapter, I provide a review of the field-experimental literature in the economics of philanthropy, with a special focus on issues like price reductions for giving and thresholds for such price reductions. Furthermore, I explain what the results suggest for the treatment of donations in the tax code.
Keywords: 300